Sobarocephala (Diptera: Clusiidae: Sobarocesphalinae)—Subgeneric classification and Revision of the New World species - Lonsdale, Owen; Marshall, Stephen A. (Zootaxa, 2012)
Sobarocephala Czerny is divided into nine newly erected species groups: the S. archisobarocephala (4 spp.), S. erwini (3spp.), S. flava (8 New World spp.; 2 Old World spp.), S. flaviseta (86 New World spp.; 1 Old World sp.), S. interrupta (86spp.), S. isla (25 spp.), S. latipennis (16 spp.), S. plumicornis (9 Old World spp.), and S. ruebsaameni (11 spp.) groups; 1species (S. setulocetra spec. nov.) remains unplaced. There are 240 species of Sobarocephala in the New World, including17 Nearctic (2 extend into the Neotropical Region) and 170 new species, some of which were previously considered va-rieties of S. humeralis Melander & Argo. The Neotropical fauna is here described, illustrated, keyed, and placed in a phy-logenetic context. Sobarocephala peruana Soós stat. nov., formerly a subspecies of S. nigronota Melander & Argo, israised to the species level, S. imitans Curran syn. nov. and S. diversipes Curran syn. nov. are synonymized with S. liturataMelander & Argo, S. annulata albiventris Soós syn. nov. is synonymized with S. annulata Melander & Argo, S. albitarsisCzerny syn. nov. is synonymized with S. humeralis, and S. pruinosa pallidor Steyskal syn. n. is synonymized with S. pru-inosa Soós. Lectotypes are designated for S. bistrigata (Kertesz) , S. lumbalis Williston, S. plumicornis Lamb and S. variegata Melander & Argo. The egg of S. uberis spec. nov. is described.